Women and science in India : a reader - Neelam Kumar; Burton, Antoinette M. (Oxford University Press, 2009)
This Reader provides a comprehensive survey of literature on women in science in India. It brings together the writings of prominent Indian academics and researchers as they discuss gender and science and explore the relevance of gender theories in the context of Indian culture, society, and politics. The inevitable association with western feminism, the status of women in research and occupation in the field of science, and the challenges faced by Indian women in line with global and universal problems are investigated in detail in the essays. The volume broadens our understanding of why, despite the existence of legal and constitutional equalities, women are subject to discrimination in science. Transcript of papers presented in a seminar and articles previously published in several journals.